Cost dan Benefit Peremajaan Kelapa Sawit Rakyat di Kabupaten Rokan Hilir - Agung Pramono (Politeknik Kampar, 2025)
The rejuvenation of smallholder oil palm plantations often encounters various challenges, including the absence of farmer institutions, loss of income from oil palm plantations, the high costs of plantation rejuvenation, and the burden of living expenses during the rejuvenation process. This study aims to analyze the financial and economic costs and benefits of smallholder oil palm plantation rejuvenation. A survey method was employed, with the research conducted in Rokan Hilir Regency, Riau Province. The sample was selected using proportional random sampling, with a total of 79 farmers as respondents. The data were analyzed using qualitative and quantitative descriptive analysis through the Cost-Benefit Analysis (CBA) approach. The findings indicate that both financial and economic aspects demonstrate that oil palm plantation rejuvenation following Good Agricultural Practices (GAP) is feasible. The financial investment criteria values are higher than the economic feasibility values, implying an improvement in farmers' welfare through plantation development.